ANALYSIS OF FINANCIAL PERFORMANCE OF NATIONAL AMIL ZAKAT INSTITUTIONS IN INDONESIA - Ani Qotuz Zuhro’ Fitriana, Isti Fadah & Novi Puspitasari (International Journal of Research Science and Management, 2019)
The purpose of this research is to measure the financial performance of national amil zakat institutions in Indonesia using financial ratios in the international standard of zakat management (iszm) approach, there are two variables in the international standard of zakat management (iszm) method, namely efficiency and capacity variables. The method used in this study is quantitative with a descriptive approach. The results of this study indicate that the financial performance of the national amil zakat institution is still volatile in terms of both efficiency and capacity variables.